Предмет: Алгебра,
автор: 1999mishkagammi
Помогите,плес,доказать тождество
Приложения:
Ответы
Автор ответа:
0
cos 2x = cos² x - sin² x = 2cos²x -1 = 1 - 2 sin² x
cos2x/(cosx + sinx) - cos2x/(sinx - cosx) = cos2x (sinx - cosx -cosx - sinx) / (sin²x - cos²x) = cos 2x * (-2cosx)/(-cos 2x) = 2cosx
cos2x/(cosx + sinx) - cos2x/(sinx - cosx) = cos2x (sinx - cosx -cosx - sinx) / (sin²x - cos²x) = cos 2x * (-2cosx)/(-cos 2x) = 2cosx
Похожие вопросы
Предмет: Математика,
автор: umbietaleva
Предмет: Английский язык,
автор: tylethecreator
Предмет: Геометрия,
автор: mariasikotuk
Предмет: Математика,
автор: супереслир
Предмет: Математика,
автор: elenaobukhova